PENGARUH KARAKTERISTIK PERSONAL, KARAKTERISTIK KERJA DAN PENGALAMAN KERJA TERHADAP KOMITMEN ORGANISASI - Untung Sriwidodo, Tri Haryanto & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT This research is conducted to know the significancy between : (1) Characteristic of Personal (age & education) to organizational comitment, (2) Job Characteristic (significance duty, skilled variation, job specification, job access information, autonomous of job) to organizational comitment (3) Job experience (year of service) to organizational comitment. Employees of Hospital population in year 2008 a number of 340 people. Sampel taken 20% with method of proporsional sampling random cluster, counted 68. The conclusion of the research: (1) Hypothesis which says: "assumpted there is a significant influence between the age to the organizational comitment" is true, (2) Hypothesis which says: "assumpted there is a significant influence between the education to the organizational comitment" is not true; (3) Hypothesis which says:"assumpted there is a significant influence between the skilled variation to the organizational comitment" is true; (4) Hypothesis which says "assumpted there is a significant influence between the job access information to the organizational comitment" is not true, and (5) Hypothesis which says "assumpted there is a significant influence between the autonomous of job to the organizational comitment" is not true. Keywords: skilled variation, job access information